News online and public opinion on Facebook during the Semenyih and Rantau by-elections - Mohamed, Shafizan; Abdul Manan, Kamaruzzaman (2019)
In response to the importance of social networking sites as sources of information, news media organizations have set up Facebook channels in which they publish news stories or links to articles. This allows for a wider news reach as well as audience participation. When audience members read and subsequently comment on news articles on Facebook, it becomes possible to identify public opinions and public sentiments on the issues being covered. Based upon this assumption, this study investigated whether there is a strong relationship between the news shared on Facebook and the public’s opinion on those news. The study broadly asked do online news set the agenda on Facebook? Content analysis was conducted on selected news and the Facebook comments on those news during the campaign weeks leading up to the Semenyih and Rantau by elections that were held in February 2019 and April 2019 respectively. The study found that while the notion of agenda setting is still strong in which the news still influenced the facebook users’ agenda, the relationship is now very much contested in that the networked environment of social media has created a more complex way to how public formed their opinions. In addition to this discovery, the study also contemplated on whether can online news effect election result?